Political Economy of Commuting Subsidies - Rainald Borck; Matthias Wrede (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
We study the political economy of commuting subsidies in a model of a monocentric city with two income classes. Depending on housing demand and transport costs, either the rich or the poor live in the central city and the other group in the suburbs. Commuting subsidies increase the net income of those with long commutes or high transport costs. They also affect land rents and therefore the income of landowners. The paper studies how the locational pattern of the two income classes and the incidence of landownership affects the support for commuting subsidies.
Keywords: R48; R14; 330; commuting subsidies; voting; monocentric city; Berufsverkehr; Subvention; Stadt-Land-Beziehung; Wohnstandort; Bodenrente; Regionale Einkommensverteilung; Public Choice; Theorie